2009
DOI: 10.1901/jaba.2009.42-895
|View full text |Cite
|
Sign up to set email alerts
|

Choice Behavior of Nonpathological Women Playing Concurrently Available Slot Machines: Effect of Changes in Payback Percentages

Abstract: In a simulated casino environment, 6 nonpathological women played concurrently available commercial slot machines programmed to pay out at different rates. Participants did not always demonstrate preferences for the higher paying machine. The data suggest that factors other than programmed or obtained rate of reinforcement may control gambling behavior, which should encourage behavior analysts to look beyond direct, contingency-driven explanations of gambling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
16
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 13 publications
5
16
0
Order By: Relevance
“…These findings were in line with those produced by Lucas and Singh (2011), in that their simulations indicated that players would not have the wherewithal to detect differences in pars, based solely on outcomes from play. Our findings were also consistent with those from problem gambling researchers, supporting the inability of players to detect differences in the pars via actual outcomes (Haw, 2008; Weatherly & Brandt, 2004; Weatherly et al, 2009). Most notably, the results of the H 0 2 tests and the time series plots fully supported the outcomes produced by prior field research aimed at the measurement of play migration (Lucas, 2019; Lucas & Spilde, 2019a, 2019b).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…These findings were in line with those produced by Lucas and Singh (2011), in that their simulations indicated that players would not have the wherewithal to detect differences in pars, based solely on outcomes from play. Our findings were also consistent with those from problem gambling researchers, supporting the inability of players to detect differences in the pars via actual outcomes (Haw, 2008; Weatherly & Brandt, 2004; Weatherly et al, 2009). Most notably, the results of the H 0 2 tests and the time series plots fully supported the outcomes produced by prior field research aimed at the measurement of play migration (Lucas, 2019; Lucas & Spilde, 2019a, 2019b).…”
Section: Discussionsupporting
confidence: 89%
“…In short, these laboratory studies failed to indicate an attenuation to differences in actual payback percentages (Haw, 2008), differences in the number of trials (Weatherly & Brandt, 2004), and sensitivity to differences in pars (Weatherly et al, 2009). In both Weatherly and Brandt (2004) and Weatherly et al (2009), the short duration of play likely influenced the results. Specifically, the limited numbers of trials on the games may have considerably affected the ability of the individuals to detect differences in the results.…”
Section: Literature Reviewmentioning
confidence: 97%
See 1 more Smart Citation
“…However, human gamblers do not always allocate responding according to the predictions of the Symbolic generalization 3 matching law (Weatherly, Thompson, Hodny, & Meier, 2009). In such cases, differential sensitivity to payback percentage suggests that slot-machine gambling can come under control of additional, rule-governed, contingencies.…”
Section: Symbolic Generalizationmentioning
confidence: 99%
“…One example of this is the matching law (Herrnstein, 1974) and its generalization (Baum, 1974), which attempts to describe how organisms distribute responding to multiple concurrent ratio or interval schedules. There is a literature on response allocation in concurrent slot machines, but findings in this area have been mixed; a number of studies (Coates & Blaszczynski, 2014;Daly et al, 2014;Dixon, Fugelsang, MacLaren, & Harrigan, 2013;Dixon, MacLin, & Daugherty, 2006;Dymond, McCann, Griffiths, Cox, & Crocker, 2012;Zlomke & Dixon, 2006) found evidence consistent with matching, but there is also evidence gamblers undermatch, showing greater (or in some cases, total) equivalence between machines that diverge either in rate of return to player or rate of reinforcement on a ratio schedule (Coates & Blaszczynski, 2013;Daly et al, 2014;Lucas & Singh, 2012;Weatherly, Thompson, Hodny, Meier, & Dixon, 2009). In addition, matching is highly susceptible to being overridden by contextual cues (Nastally, Dixon, & Jackson, 2010;Zlomke & Dixon, 2006) although this appears to weaken with extended exposure to the contingencies of a machine (Hoon & Dymond, 2013).…”
Section: Behavioural Mechanismsmentioning
confidence: 99%